ChemInform Abstract: Sr2MgOsO6: A Frustrated Os6+(5d2) Double Perovskite with Strong Antiferromagnetic Interactions. Issue 25 (5th June 2015) - Sarapulova, Angelina; Adler, Peter; Schnelle, Walter; Mikhailova, Daria; Felser, Claudia; Tjeng, Liu Hao; Jansen, Martin
Abstract: The Os 6+ (t2g 2 ) double perovskite Sr2 MgOsO6 is prepared by solid state reaction of stoichiometric amounts of SrO2, OsO2, and MgO under intermittent regrinding and final oxidation (1.